Rola wskaźników realizacji trwałego rozwoju - Śleszyński, Jerzy (The meaning of indicatros for sustainable development, 2007)
The paper is aimed at a comprehensive presentation of sustainability indicators considered as a crucial element in monitoring sustainable deyelopment. The author argues that multidimensional problem like sustainable deyelopment needs an adeąuate monitoring approach using diverse and specific indicators. A typology proposed in the paper distinguished cross-cutting indicators, synthetic indicators, and indicators created for local communities. In the conclusion part of the paper, the list of arguments specifies social, political, and pragmatic reasons why sustainability indicators should be more commonly and widely used.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 99-113